Nurturing Anti-Corruption Culture through Pedagogical Strategies in Private Islamic Religious Universities in Tangerang - Deden Saeful Ridhwan; Maemunah Maemunah; Ahmad Buchori Muslim; Siti Marpuah (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
The anti-corruption education program initiated by the government and the Corruption Eradication Commission (KPK) involves various elements of institutions and ministries targeting its implementation in educational units ranging from basic education to higher education. Higher education institutions, both public and private, are the object of the implementation of this anti-corruption education. This study aims to explorethe strategy of Private Islamic Religious Universities (PTKIS) in Tangerang in nurturing anti-corruption culture in the institutions. This research was carried out through aqualitative approach employingfield studies at PTKIS in Tangerang. Data collection includedinterview, observation and documentation. Data was then analyzed descriptivelythrough the stage of individual case analysis and continues with multi-site analysis.The results of this study show that the nurturingof anti-corruption culture in PTKIS is carried out through several strategies. First, the integration of anti-corruption education in the curriculum, either as lecture material or as a separate course. Second, the internalization of anti-corruption values in campus life in the form of honesty, discipline, responsibility and integrity. Third, a credible and transparent financial management system through a centralized financial management system, transparency of financial management, and financial audits by professional and credible external parties.